Socio-Economic Policy and Youth Unemployment in Nigeria: An Assessment of Ekiti State Youths for Commercial Agriculture Development Programme (YCAD) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The place and the important of youth in the development of any country cannot be over emphasized.This study seeks to examine the impact of Ekiti State policy on Youths for Commercial Agriculture Development Programme (YCAD) on job creation and youth empowerment in the state. Survey research design was adopted in this study. Data for this study were generated through both primary and secondary sources. The primary source of data includes questionnaire and interview conducted among unemployed beneficiaries of YCAD. Data collected were analyzed using descriptive methods involving tables and percentages. The findings of the study reveals that YCAD programmes, like any other government policy surfer implementation gap and as a result, have not impacted significantly on the well-being of Ekiti youths. The paper therefore, recommended amongst others that government should improve access to social amenities such as feeder roads, electricity and regular water supply to enhance their well-being. Also the government should ensure prompt release of fund and other equipment directly to the beneficiary of the programme, this would enhance youths’ participation in agricultural development programme.